UJI EFEKTIVITAS EKSTRAK ETANOL DAUN LAMUN (Cymodocea rotundata) TERHADAP PENURUNAN KADAR GLUKOSA DARAH TIKUS DIABETES MELITUS - Andi Emelda; Aulia Wati; Besse Yulismayanti; Dewi Yuliana (Fakultas Farmasi UMI, 2022)
Diabetes mellitus is a disease caused by a glucose metabolism disorder due to lack of insulin indicated by high levels of glucose in the blood due damage in pancreatic 3 cells or insulin resistance. The research aimed to determine the effect and effective dosage of ethanol extract of seagrass to decrease glucose levels of diabetic mellitus in rats. It used 15 rats divided into 5 treatment groups, namely negative groups (NaCMC), positive group (Glibenclamide), tested extract group with the doses of 0,25 g/kgBW, 0,5 g/kgBW and 0,75 g/kgBW respectively. Alloxan induction at a dose of 0,13 g/kgBW was given intraperitoneally once a day orally for 14 days. Blood glucose level measurement was carried out before induction, after induction and after glucometer therapy. The result was statistically analyzed using the One Way Anova followed by the Bonferoni Post Hoc test and showed that the ethanol extract of seagrass leaves had a deep effect in reducing the blood glucose level of rats induced by alloxan at 750 mg/kgBW as the effective dose.